Elucidating the Eucharist. Issue 3 (27th May 2019) - Hewitt, Simon
ABSTRACT: The doctrine of the Real Presence of Christ in the Eucharist presents a particular challenge to its defenders: how is it so much as intelligible? This paper explores Dummett's response to this question, centred on the notion of deeming. Whilst instructive, Dummett's position is unsustainable as it stands, since it fails to secure the meaningfulness of the doctrine. Once deeming is brought together with an account of bodiliness and an appreciation of the nature of the Eucharist as a meal, however, the way is open to demonstrating the intelligibility of the doctrine. This is a prerequisite even for its rejection as false.